Language Politeness in the Speech of Cinta Subuh Film Directed by Indra Gunawan - Antika, Aulia Putri; Azizah, Aida (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
This study attempts to describe the principles of politeness that are adhered to and violated in Indra Gunawan's film "Cinta Subuh", especially in the principles of politeness in language. This research method uses a qualitative method with a pragmatic approach. Indra Gunawan's film "Cinta Subuh" is the basis for research data; allegedly obeying and violating the principles of politeness. Information collected through note-taking and listening strategies. Data analysis uses normative methods. The norms used are politeness norms in the form of norms that are obeyed and violated according to the principles of politeness. The results of this research show that data contains (1) bidals that comply with the principles of politeness in the film "Cinta Subuh". The thimbles that are obeyed are the thimbles of feeling, the thimbles of generosity, the thimbles of favor, the thimbles of humility, and the thimbles of sympathy, (2) the thimbles that violate the principle of politeness in the film "Cinta Subuh". There are transgressions against the thimbles of feeling, generosity, favor, humility, and agreement.